2022
DOI: 10.2196/34451
|View full text |Cite
|
Sign up to set email alerts
|

Findings and Guidelines on Provider Technology, Fatigue, and Well-being: Scoping Review

Abstract: Background Video and other technologies are reshaping the delivery of health care, yet barriers related to workflow and possible provider fatigue suggest that a thorough evaluation is needed for quality and process improvement. Objective This scoping review explored the relationship among technology, fatigue, and health care to improve the conditions for providers. Methods A 6-stage scoping review of literat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…While Zoom fatigue has been described and some studies have measured it among health care providers, little research has explored the phenomenon in patient populations or its impact on the quality of telemedicine visits. (17)(18)(19) This issue may be particularly relevant to younger populations who continue to engage in distance learning or in adults who telecommute.…”
Section: Discussionmentioning
confidence: 99%
“…While Zoom fatigue has been described and some studies have measured it among health care providers, little research has explored the phenomenon in patient populations or its impact on the quality of telemedicine visits. (17)(18)(19) This issue may be particularly relevant to younger populations who continue to engage in distance learning or in adults who telecommute.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, psychosocial factors and psychological variables were not considered in the present study, even though previous studies have related severe DES and DED symptoms to stress, anxiety, depression, and somatic disorders such as headache and insomnia. 28,29 However, this study contributes significantly to the literature despite the above limitations. We showed a rising concurrent correlation between DES and DED symptoms and first revealed that patients with higher digital eye strain symptoms are exposed to developing more severe dry eye disease.…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…Lastly, psychosocial factors and psychological variables were not considered in the present study, even though previous studies have related severe DES and DED symptoms to stress, anxiety, depression, and somatic disorders such as headache and insomnia. 28 , 29 …”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Many of the surveyed papers studied HOFs using specific technologies including mental health consultation [20,21], online consultations [22,32], clinical decision support systems (CDSS) [23], electronic medication management systems [24], video consultation [25][26], aged care systems [27] and telemedicine [36]. The context of use for these systems included hospitals [23,[28][29][30][31][32][33][34], residential aged care homes [27], and community health facilities [35]. Eleven papers were review papers and described a range of technology, users, and processes [20-22, 26-27, 31, 37-41].…”
Section: Structuresmentioning
confidence: 99%
“…ODH is about broader health system goals such as coordination and communication, but system design often focuses on support for micro level tasks and outcomes such as efficiency. Broader system level outcomes as patient safety, enhancement of team-based care, and prevention of provider burnout will not be achieved unless we explicitly design and evaluate systems to support those goals [28,31]. Prevention of provider burnout and fatigue has to go beyond the design of technology at the individual level and must be evaluated with macro goals like the Quadruple Aim in order to support providers' well-being and to prevent workload burden, fatigue, and burnout [31].…”
Section: Macromentioning
confidence: 99%